PROSES DECISION TREE PADA DATAMINING DENGAN ALQORITMA ID3 - MUCHLIS, LITA SARI (IAIN Batusangkar, 2010)
This article was study about decision process data meaning with algoritma ID3. Data meaning is an atomatic extraction process of large data. It was found with a contour data. Data meaning have a function to produce a different contour wich other. The function of classification of data meaning is helping write decision tree, the function with algoritma ID3.Key words: data meaning, classification, decision tree